2021
DOI: 10.1089/photob.2020.4913
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of an Augmented Intense Pulse Light Protocol for Dry Eye Syndrome and Blepharitis

Abstract: Objective: We evaluated the safety and efficacy of an augmented BroadBand Light (BBLÔ) protocol on the upper and lower eyelids in improving meibomian gland dysfunction (MGD) and/or dry eye disease (DED). Background: DED, often associated with MGD, can cause significant morbidity and accounts for 3.54 billion U.S. dollars of health care spending yearly. Intense pulsed light (IPL) has been used to treat MGD DED with some success. BBL therapy, a high-quality IPL machine, shows much promise for decreasing inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 27 publications
3
25
0
Order By: Relevance
“…This non-comparative prospective case series has shown, as in previous studies, that IPL-based therapy can be an effective treatment for dry eye with MGD associated [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. In agreement with the mechanism of action of the IPL technology, a significant change was observed in the secretion of the meibomian glands, with more eyes showing clear or yellow secretions after therapy.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This non-comparative prospective case series has shown, as in previous studies, that IPL-based therapy can be an effective treatment for dry eye with MGD associated [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. In agreement with the mechanism of action of the IPL technology, a significant change was observed in the secretion of the meibomian glands, with more eyes showing clear or yellow secretions after therapy.…”
Section: Discussionsupporting
confidence: 88%
“…All these clinical changes after IPL were associated to an improvement of symptomatology evaluated by means of the OSDI score, as in previous studies using IPL for the treatment of dry eye with MGD [6,[10][11][12][13][14][15][16]. This change in OSDI with IPL was significantly correlated with the level of baseline OSDI, with more potential of improvement in those eyes with severe dry eye-related disturbances.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Although the exact mechanism of action remains unknown, many studies since then have reported significant improvements in dry eye symptoms, tear break-up times, lipid layer grade and thickness, and/or meibomian gland function, with limited adverse events. 2,[15][16][17][18][19][20][21][22][23] These studies have used a variety of IPL devices, including M22™ (Lumenis, Israel), 17,20,22 Quadra Q4 (DermaMed Solutions, USA), 2,14 E>Eye (E-SWIN, France), 15,16,18,21 and customized treatment protocols, ranging in energy levels, treatment frequencies, number of treatment sessions and treatment durations.…”
Section: Introductionmentioning
confidence: 99%
“…BroadBand Light (BBL™) is a high-quality, enhanced IPL modality that uses polychromatic, noncoherent, continuous light waves from the visible (420 nm) to the infrared (1400 nm) spectrum. 23 BBL-IPL is known for its relative safety, high skin coverage rate, and minimal recovery time. 20 As compared to IPL alone, BBL offers larger spot sizes, a wider range of filters and a continuous pulsing mode, which enhance the efficacy and safety of treatments.…”
Section: Introductionmentioning
confidence: 99%